Genetic and environmental determinants of 25-hydroxyvitamin D levels in multiple sclerosis - Laursen, Julie H; Søndergaard, Helle Bach; Albrechtsen, Anders; Frikke-Schmidt, Ruth; Koch-Henriksen, Nils; Soelberg Sørensen, Per; Sellebjerg, Finn; Oturai, Annette (Multiple sclerosis, 2015)
Background: Evidence is accumulating supporting a beneficial effect of vitamin D in multiple sclerosis (MS). Genome-wide association studies (GWAS) have shown significant associations between 25-hydroxyvitamin D (25(OH)D) and single nucleotide polymorphisms (SNPs) in key genes in the vitamin D metabolism. Objective: To examine the association between 25(OH)D and six GWAS SNPs and environmental factors in 1497 MS patients. Methods: Blood samples and lifestyle questionnaires were collected between 2009 and 2012. Genotyping of GC-, CYP2R1- and NADSYN1-SNPs was performed by TaqMan allelic discrimination (Life Technologies). Results: We found significant associations between 25(OH)D and SNPs in GC (rs7041, p = 0.01 and rs2282679, p = 0.03) and CYP2R1 (rs10741657, p =1.8 × 10−4). Season of blood sampling (p = 2.8 × 10−31), sex (p = 1.9 × 10−5), BMI (p = 2.3 × 10−5), vitamin supplements (p = 7.0 × 10−22), and fish intake (p = 0.02) also had significant effects on 25(OH)D. Conclusion: In this cross-sectional study, we found significant effects of environmental factors and SNPs in GC and CYP2R1 on 25(OH)D in MS patients. Since 25(OH)D might have protective effects in MS, and vitamin D supply is a modifiable factor, it may be important to include this in the MS treatment regimen.